GENETIC INVOLVEMENT OF INTERLEUKIN 4 FOR ASTHMA AND IDENTIFICATION OF POTENTIAL PHYTOCHEMICAL SCAFFOLD THROUGH MOLECULAR DOCKING STUDIES - Sarithamol, S.; V., Divya; R., Sunitha V.; Surendran, Suchitra; Pushpa, V. L.; Manoj, K. B. (International Journal of Current Pharmaceutical Research, 2018)
Objective: Interleukin 4, an important cytokine, has the major role in the immunomodulatory responses associated with asthma. The present study focused on the involvement of single nucleotide polymorphism variation (SNP) of interleukin 4 (IL4) in the development of disease, asthma and designing small molecules for the inhibition of IL4 through in silico strategy. Methods: Identification of disease causing SNP will be a wise approach towards the phenotype specific treatment. A human origin deleterious no synonymous SNP of IL4 were found out in the chromosome region 5q31-q33 (rs199929962) (T/C). Proteins of the corresponding nucleotide variation were identified and were subjected to characterization studies for selecting the most appropriate one for further mutational analysis and molecular docking studies. Results: Influence of microbes on SNP variation of IL4 gene leading to asthma was found to be insignificant by metagenomic studies. Gene responsive drugs were identified through environmental factor analysis. The drug candidates including corticosteroids were subjected to protein interaction studies by in silico means. The pharmacophoric feature derived from drug receptor interaction was utilized for virtual screening on a dataset of anti-inflammatory phytomolecules. The scaffolds of ellagic acid and quercetin were identified as potential nonsteroidal entities which can shield the asthmatic activities. Conclusion: Developing small molecules using these scaffolds taking interleukin 4 as a target will be an adequate solution for steroid resistant asthma.